What is the physical and mental health status of individuals playing tennis recreationally during the pandemic process? - Güler, Melek; Abdioğlu, Mekki Abdioğlu (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aim of our study is to investigate the physical and psychological state of individuals who play tennis recreationally during the pandemic process. 206 individuals who have been playing tennis recreationally for at least 1 year participated in the study. As a data collection tool, demographic information questionnaire, International Physical Activity Questionnaire-Short Form (IPAQ-SF), and SF-12 Brief Health Questionnaire were used. The data were analyzed in 2.0.0 Jamovi statistics program; Descriptive statistics were analyzed using Mann Whitney U test, Kruskal Wallis test, and ANCOVA test. According to the findings of the study, there was no statistically significant difference between the groups in the physical and mental health scores of the participants according to the MET level (p>0.05). Men’s physical health mean scores and women’s mental health scores were higher. Physical health mean scores of non-smokers were higher than smokers, and there was a statistically significant difference in favor of non-smokers in physical health scores (p<0.05). As a result, the physical and psychological conditions of individuals who play tennis recreationally are generally at a good level. During the pandemic period individuals may be advised to play tennis.